Peran Pemerintah Desa dalam Pengembangan Desa Wisata Nagrog, Kecamatan Cipatujah, Kabupaten Tasikmalaya - Smesta, Bagas Lanang; Khadijah, Ute Lies Siti; Pamungkas, Kasno (International Forum of Researchers and Lecturers, 2025)
This research explores the role of the Nagrog Village Government in advancing the Nagrog Tourism Village located in Cipatujah District, Tasikmalaya Regency. Utilizing a qualitative approach with a case study method, data were gathered through in-depth interviews, direct observations, and literature reviews. The study's results indicate that the Nagrog Village Government holds a pivotal role in the tourism village's development by improving coordination with Pokdarwis and BUMDes, implementing Village Regulations (Perdes) as a legal framework, and enhancing tourism-related infrastructure. Despite these efforts, challenges persist, including the lack of long-term development plans, insufficient support for Micro, Small, and Medium Enterprises (MSMEs), and ineffective promotional strategies. While the management of Tonjong Canyon as the main attraction has positively influenced the local economy, its contribution to Village Original Income (PAD) remains minimal. To achieve sustainable tourism village development, it is crucial to strengthen strategic planning, maximize digital marketing efforts, and improve MSME support.